2019
DOI: 10.1007/s11896-019-09342-5
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Forensic Child Interviewing in Child Sexual Abuse Cases in Indonesia

Abstract: Most of the foregoing research on child investigative interviewing has focused on interview practices in Western countries, thus potentially limiting the generalizability and application of the findings to improve interview practices in non-Western countries. The current studies are the first to examine police interviewing practices involving alleged child sexual abuse (CSA) victims in Indonesia which has marked cultural differences compared with Western countries. In Study 1, we presented Indonesian police ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…Baldwin 1993). For instance, a study conducted by Sumampouw et al (2020) in Indonesia, a neighbouring country that shares many cultural similarities with Malaysia, reported that police interviewers who have not been trained in an evidence-based protocol used directive and option-posing questions extensively in child forensic interviewing. It is now established that tactics such as maximisation and situation futility are problematic in that they increase a one's susceptibility to false confessions (Kassin 2014), whereas the use of leading or suggestive questions that implies a desired response tends to yield information of poorer quality (Loftus 2005;Sharman and Powell 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Baldwin 1993). For instance, a study conducted by Sumampouw et al (2020) in Indonesia, a neighbouring country that shares many cultural similarities with Malaysia, reported that police interviewers who have not been trained in an evidence-based protocol used directive and option-posing questions extensively in child forensic interviewing. It is now established that tactics such as maximisation and situation futility are problematic in that they increase a one's susceptibility to false confessions (Kassin 2014), whereas the use of leading or suggestive questions that implies a desired response tends to yield information of poorer quality (Loftus 2005;Sharman and Powell 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to indicate whether they thought each statement is ‘true’ or ‘false’, or they could select the ‘don't know’ option. Of the 20 statements, 19 are false based on broad scientific consensus (see Erens et al, 2020; Sumampouw et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This cultural diversity undoubtedly has influence on the way crimes are reported and investigated. For instance, Sumampouw et al (2020Sumampouw et al ( , 2021 in their studies among Indonesians put forward that culture may very well influence how events are remembered as well as how people interact with children.…”
mentioning
confidence: 99%
“…This effort should start with an awareness of the impact of culture on child forensic interviews (Hamilton et al, 2016). For example, recent research on child interviewing practices in Indonesia has shown that police officers mostly ask closed questions (Sumampouw et al, 2019). This finding together with the cultural dynamics to not talk about issues such as abuse in Indonesia warrants the need for sophisticated rapport building.…”
Section: Commentary 7 Cultural Aspects In Child Forensic Interview: An Indonesian Contextmentioning
confidence: 99%